Designing workspace for better performance, safety and health in manufacturing industry, an ergonomics case study - Mohammad Norhafizi, Mohamed Yusof (2007)
In manufacturing industry there are so many things happen. Human works in specific workspace and use what ever provided by the company. Therefore, it is necessary to provide good design of workspace in order to maximize the utilization of tools and improving the productivity. Thus, the research is carried out for identified the improvement of the current workspace. The research of designing workspace for better performance, safety and health is about identified potential problem and make improvement toward some adjustment. The focusing aspect in this research are design of seat, height of computer screen, height of mouse and procedure of worker while perform their task. In this research, the new design is develop by using theory of workspace design. Method to be use in this research is by observation and questionnaire. For intangible data questionnaire will be used and for tangible data observation by referring to the theory will be use. Anthropometry data of workers will be use to make improvement of current design in order to make sure the new design is suitable for them. The final stage of this research is implementing the new design of the workspace. After implementation expected result is the productivity, safety and health of the current design able to increase and enhance the satisfaction of the workers.